Pre-operative physiotherapy and short term functional outcome of primary total knee arthroplasty - Ismail, Mohd Shukry; Ahmad Shokri, Amran; Sharifudin, Mohd Ariff; Ab Rahman, Shafuzain (2013)
Background: The significant impact of pre-operative physiotherapy on the functional outcomes of arthroplasty surgery is still a subject under study. This study has been designed to evaluate the effect of pre-operative physiotherapy on the short-term functional outcome of primary total knee arthroplasty. Methods: This randomized controlled trial involved a total of 50 patients with primary knee osteoarthritis who underwent unilateral primary total knee arthroplasty at a single tertiary centre. The physiotherapy group (n = 24) performed physical therapy exercise for six weeks immediately prior to surgery. No pre-operative physiotherapy subjected to the other 26 patients (non-physiotherapy group). Post-operatively, all patients went through similar physiotherapy regime in the rehabilitation period. Assessment was done at three intervals; pre-operation, six weeks and three months post-operatively. The algo-functional Knee Injury and Osteoarthritis Outcome Score (KOOS) was used as the primary outcome measurement tool. The difference of post-operative range of motion was compared between the two groups. Result: Both groups showed significant difference for all KOOS subscales (p-value <0.001). The mean score difference at six weeks and three months was not significant in Sports and Recreational Activities subscale for both groups (p-value >0.05). The time-group interaction analysis showed significant difference only for Symptoms and Daily Living Activities between groups (p-value <0.05). There was no significant difference with regards to time in Pain, Sport and Recreational Activities and Quality of life between groups (p-value >0.05). The range of motion difference was significant within both treatment groups (p-value <0.001). The pre-operative and three months range of motion showed no significant difference in both treatment groups (p-value >0.05). Time-group analysis also showed no significant difference of ROM between the two groups (p-value 0.928). Conclusion: A six week pre-operative physiotherapy has no significant impact on the short-term functional outcomes and range of motion following primary total knee arthroplasty.